KNOWLEDGE, ATTITUDES, AND BEHAVIOR OF THE COMMUNITY IN USING SUPPLEMENTS DURING THE COVID-19 PANDEMIC - Yeni Farida; Rasmaya Niruri; Adi Yugatama (Jurnal Farmasi Sains dan Praktis, 2022)
The Covid-19 pandemic has been responded to various attitudes and behaviors related to its prevention. Understanding certain information makes a person make the right decision. Misunderstanding the improvement of the immunity system and prevention of COVID-19 may lead to inappropriate attitudes and behaviors in using supplements in society. This study aims to describe the level of knowledge and attitudes toward using health supplements and the consumption of health supplements during the Covid-19 pandemic. The research design is a cross-sectional study using primary data based on data collection by questionnaire. The research subjects were visitors of Jamsaren and Riyadh pharmacies in September 2020 who were more than 17 years old, could read and write, and were willing to be respondents. Knowledge is assessed by each correct answer marked 1, and then the total is compared with the total score multiplied by 100%. The level of knowledge is classified based on the score obtained; poor knowledge (score <70) and good (>70). Attitudes are classified into panic and non-panic. Behavior was analyzed descriptively. The results on 132 subjects showed that most of the respondents (78%) still had less knowledge of using health supplements to prevent Covid-19. The Chi-Square test results obtained a p-value of 0.312 (p > 0.05), meaning no significant difference in knowledgeable or good knowledge in respondents' responses. The attitude variable affects the respondent's behavior, as evidenced by the p-value of 0.008 (p <0.05). The predominant health supplement is vitamin C from pharmacies on their initiative